THE RELATION BETWEEN ROTATION AND TRAINING AGAINST EMPLOYEE’S PERFORMANCE - Widya; Parlagutan Silitonga (Human Capital Development, 2015)
Purpose- Rotation and training are two areas of problem and solution to human resource manager. This research was conducted to measure how are the effect of rotation and training toward the employee’s performance in a hospitality industry, and in thgis case study at Katsusei Resaurant. Design/methology/approach- A questionaire survey to employees in Katsusei Restaurant within a single organization supported by interviews. Findings- There are positive direct effects between rotation, and training on employeee’s performance. However, other vriables that not included in surevey are still influenced the posibl better performace of employee. When rotation and training are held for the benefit of the employee to achieve the company’s goals, the planned, and agreed mutation and training are positively increasing the employee’s performance. Research limitations- Due to a single company, and limited staffs, this research need to be evaluated. On the other hand, the two variables did not represented the whole factors of performance. Practical implications-The manager of human resource shall communicate rotation and training prior to a definite planning, and executions Originality/value- Ratation and training have been proved as a part of human capital both for employees, and company/organization